Clinical Study of Urinary Tract Tumors in Patients with Maintenance Dialysis for End Stage Renal Disease - Xu, Chang-Li; Xu, Hui; Song, Jin-Qi; Zhou, Ya-Nan (Nepalese Journal of Cancer, 2019)
Introduction: The research in the past ten years shows that the incidence of malignant tumors in dialysis patients is significantly higher than that in normal people. The highest proportion of urinary tumors is one of the main causes of death in patients with end-stage renal disease, and the incidence is gradually increasing. However, the high-risk factors of urinary tract tumors in dialysis patients have not yet been fully elucidated, so exploring this issue is an important issue that the medical community needs to solve. The objectives of this study are to understand the clinical characteristics of maintenance dialysis patients with urinary tract tumors and the influence of related factors on their prognosis. Methods: The clinical data of 22 patients with urinary tract tumors in maintenance dialysis (MHD) from the Affiliated Hospital of Chengde Medical College from January 2013 to June 2018 were retrospectively analyzed. The incidence of urinary tumors and clinical diagnosis and treatment were investigated. And prognosis, analysis of the impact of various relevant factors on the overall survival of patients with dialysis and urinary tumors. Results: The 912 patients with maintenance dialysis, 22 patients had urinary tumors with an incidence of 2.41%. Among them, 13 patients were bladder tumors, 7 patients were renal or ureteral tumors, 1 patient was renal tumor, and 1 patient was prostate cancer. There were 17 cases of intermittent and painless gross hematuria, 2 cases of gross hematuria, 1 case of lumbar pain, 1 case of abdominal pain and dysuria, 1 case of frequent urination and dysuria. Ten patients underwent surgery, and 4 patients died. The postoperative survival of the patients was 12~103 months, with an average of 58.75 months. 12 patients were unable to undergo surgery because of other diseases or economic reasons; in 9 the disease was found during autopsy. The time from tumor to death was 14~38 months, with an average of 24.11 months. The causes of death in 13 death patients: 5 patients were myocardial infarction, 3 patients were heart failure, 3 patients were tumor metastasis, and severe sepsis in 2 patients. Conclusion: There is increased propensity of GU tumors in maintenance dialysis patients. The tumors are of higher grade and demonstrate poor prognosis. Therefore, attention should be paid to the monitoring of urinary tract tumors in maintenance dialysis patients, especially elderly patients without cardiovascular and cerebrovascular complications, because their life expectancy can be longer.